2009
DOI: 10.1002/ajmg.a.32716
|View full text |Cite
|
Sign up to set email alerts
|

Developmental anomalies with features of disorganization (Ds) and amniotic band sequence (ABS): A report of four cases

Abstract: Disorganization (Ds) is a mouse mutant in which heterozygotes manifest defects in various organ systems including cranioschisis, hamartomas, limb abnormalities, body wall defects, eye defects, and craniopharyngeal defects. We report four patients with developmental anomalies that are seen in amniotic band sequence (ABS) with additional anomalies that could not be explained by amniotic bands alone. The anomalies seen in our patients included facial malformation and clefting, brain anomalies (encephalocele, agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
(71 reference statements)
0
10
0
1
Order By: Relevance
“…Split genital papilla, in the presence of an intact body wall, and segmental duplication of the gut were not reported in any ABS/HEDs patients. Microphthalmia was not uncommon in the Ds mouse and was reported in several ABS/HEDs patients [Donnai and Winter, 1989, Case 5; Purandare et al, 2009, Cases 3 & 4]. However, in all three patients there was either severe disruption of the entire frontal brain and face, and/or direct disruption of the ocular region by bands.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…Split genital papilla, in the presence of an intact body wall, and segmental duplication of the gut were not reported in any ABS/HEDs patients. Microphthalmia was not uncommon in the Ds mouse and was reported in several ABS/HEDs patients [Donnai and Winter, 1989, Case 5; Purandare et al, 2009, Cases 3 & 4]. However, in all three patients there was either severe disruption of the entire frontal brain and face, and/or direct disruption of the ocular region by bands.…”
Section: Resultsmentioning
confidence: 64%
“…Cranial defects that are not uncommon in ABS were present in a number of the cases. Several patients could be classified as having limb‐body wall defect (LBWD) as defined by Van Allen et al [1987] [Graham et al, 1981, Case 1; Donnai and Winter, 1989, cases 2 & 4; Elliot et al, 1995; Purandare et al, 2009, Case 4]. Bands and adhesions are a common feature of LBWD and Van Allen et al [1987] suggested vascular compromise as the pathogenesis for LBWD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recurrence in this family could be explained by a recessive pattern, but no increased prevalence of consanguinity is found in sirenomelia, and in the familial reports renal anomaly or imperforate anus were described in first‐degree relatives, suggesting a dominant pattern of inheritance with low penetrance [Rudd and Klimek, 1990; Selig et al, 1993], with one asymptomatic mother [Selig et al, 1993] and a father with few symptoms [Rudd and Klimek, 1990], with narrow inter‐pediculate distance. Our preferred hypothesis then is a dominant major gene with variable expression potentially due to genetic modifier genes, environmental effects or epigenetic repercussions (diet, toxins, hyperglycemia…), as in the mouse model “disorganization” (Ds), in which there is a spontaneous mutation in an inbred strain of mice, with random occurrence of multiple defects with extreme variability in a semi‐dominant manner [Hummel, 1958; Crosby et al, 1993; Isidor et al, 2009; Purandare et al, 2009; Hunter, 2011]. The Ds gene has been located on mouse chromosome 14, but remains elusive [Crosby et al, 1993; Hunter, 2011].…”
Section: Discussionmentioning
confidence: 99%